2001
DOI: 10.1046/j.1528-1157.2001.18800.x
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate Rapidly Raises Brain GABA in Epilepsy Patients

Abstract: Summary: Purpose:The short-and long-term pharmacodynamic effects of topiramate (TPM) on brain ␥-aminobutyric acid (GABA) metabolism were studied in patients with complex partial seizures.Methods: In vivo measurements of GABA, homocarnosine, and pyrrolidinone were made of a 14-cc volume in the occipital cortex using 1 H spectroscopy with a 2.1-Tesla magnetic resonance spectrometer and an 8-cm surface coil. Fifteen patients (four men) were studied serially after the first, oral dose (100 mg) of TPM.Results: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 50 publications
1
58
0
2
Order By: Relevance
“…Two psychophysical studies have shown that performance on visual tasks mediated by the activity of GABAergic interneurons is significantly correlated with GABA content in the primary visual cortex as measured by 1H-MRS using a MEGA-PRESS sequence Yoon et al 2010a). In addition, several studies have shown that anticonvulsant medications that appear to increase GABAergic tone cause an increase in brain GABA as measured with 1H-MRS (Weber et al 1999;Petroff et al 2001). It is worth noting that several studies have found evidence that the 1H-MRS GABA signal varies over the course of the menstrual cycle in women, with GABA signal reduced during the luteal phase (Epperson et al 2002;Harada et al 2010).…”
Section: Gabamentioning
confidence: 99%
“…Two psychophysical studies have shown that performance on visual tasks mediated by the activity of GABAergic interneurons is significantly correlated with GABA content in the primary visual cortex as measured by 1H-MRS using a MEGA-PRESS sequence Yoon et al 2010a). In addition, several studies have shown that anticonvulsant medications that appear to increase GABAergic tone cause an increase in brain GABA as measured with 1H-MRS (Weber et al 1999;Petroff et al 2001). It is worth noting that several studies have found evidence that the 1H-MRS GABA signal varies over the course of the menstrual cycle in women, with GABA signal reduced during the luteal phase (Epperson et al 2002;Harada et al 2010).…”
Section: Gabamentioning
confidence: 99%
“…In the rat, neither gabapentin nor pregabalin increases GABA levels (Sills et al, 2003;Errante and Petroff, 2003), although small increases have been reported with gabapentin in human brain tissue slices (Errante et al, 2002). [Increases in GABA also were seen in human neocortex with topiramate (Petroff et al, 2001) and lamotrigine (Kuzniecky et al, 2002) which are not known to alter the synthesis or metabolism of GABA.] Since both gabapentin and pregabalin are effective anticonvulsants in the rat, it is clear that GABA-T inhibition is not necessary for anticonvulsant activity in the model systems where it has been tested.…”
mentioning
confidence: 99%
“…Topiramate can increase MR spectroscopyϪdetected GABA by 72% or 0.9 mmol/L in as little as 3-4 hours as well as its precursor, glutamine. [85][86][87][88] Lamotrigine, of the newer generation of AEDs, has proved very useful in other conditions such as bipolar disorder. Despite its efficacy in seizure prevention, 89 MR spectroscopy showed no GABA effect for lamotrigine acutely but revealed significant GABA increases of one-quarter at 1 month.…”
Section: Management Of Seizure Disorders Relies On the Preventive Funmentioning
confidence: 99%